2013
DOI: 10.1021/bi400294e
|View full text |Cite
|
Sign up to set email alerts
|

Human UDP-α-d-xylose Synthase Forms a Catalytically Important Tetramer That Has Not Been Observed in Crystal Structures

Abstract: Human UDP-α-d-xylose synthase (hUXS) is a member of the extended short chain dehydrogenase/reductase (SDR) family of enzymes. Previous crystallographic studies have shown that hUXS conserves the same dimeric quaternary structure observed in other SDR enzymes. Here, we present evidence that hUXS also forms a tetramer in solution that is important for activity. Sedimentation velocity studies show that two hUXS dimers undergo a concentration-dependent association to form a tetramer with a Kd of 2.9 μM. The tetram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
5
11
0
Order By: Relevance
“…The widths of the peak and the tailing at both low and high s values were previously shown to indicate the presence of a small amount of monomer and tetramer in rapid equilibrium with the dimer (Figure 2A). 15 At the same concentration of protein, hUXS R236H sediments as a broad peak at a lower value of 3.4 S, close to the theoretical value for the hUXS monomer (3.3 S) ( Figure 2A). This confirms our earlier prediction that the mow mutation would weaken the dimer.…”
Section: ■ Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The widths of the peak and the tailing at both low and high s values were previously shown to indicate the presence of a small amount of monomer and tetramer in rapid equilibrium with the dimer (Figure 2A). 15 At the same concentration of protein, hUXS R236H sediments as a broad peak at a lower value of 3.4 S, close to the theoretical value for the hUXS monomer (3.3 S) ( Figure 2A). This confirms our earlier prediction that the mow mutation would weaken the dimer.…”
Section: ■ Resultssupporting
confidence: 76%
“…6 We have also shown that hUXS dimers undergo a concentration-dependent association to form a tetramer, which represents the catalytically important oligomeric state of hUXS. 15 This result prompted us to examine the structural consequences of the mow mutation in detail. Here we show that the R236H substitution weakens the dimeric complex as expected ( Figure 2A).…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, a systematic search of K d values is carried out to determine the optimal relative fractions of A, B and AB that minimize the goodness‐of‐the‐fit chi‐squared between the resulting theoretical scattering profile and the experimental one using Eqns . This approach enables the testing of alternative structural models for a protein–ligand complex .…”
Section: Saxs Analysis Of a Protein–ligand Equilibriummentioning
confidence: 99%